2005
DOI: 10.1557/jmr.2005.0403
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of magnetite particle size on adsorption and desorption of arsenite and arsenate

Abstract: Numerous studies have examined arsenic adsorption on varying adsorbents including iron oxides, aluminum hydroxides, alumina, and carbon as a means of arsenic removal in drinking water treatments. The objectives of this study were to evaluate the effect of magnetite particle size on the adsorption and desorption behavior of arsenite and arsenate, and to investigate the competitive adsorption between natural organic matter (NOM) and arsenic. Increases in adsorption maximum capacities for arsenite and arsenate we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
204
5
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(238 citation statements)
references
References 45 publications
15
204
5
2
Order By: Relevance
“…This work also uses commercially available nanoscale iron oxides. While these materials are more polydisperse, large amounts are available and the two sizes (20 and 300 nm) are readily suspended in water [12,13]. In addition to a difference in size, these commercial materials are also more aggregated in suspension than the laboratory-prepared materials.…”
Section: Resultsmentioning
confidence: 99%
“…This work also uses commercially available nanoscale iron oxides. While these materials are more polydisperse, large amounts are available and the two sizes (20 and 300 nm) are readily suspended in water [12,13]. In addition to a difference in size, these commercial materials are also more aggregated in suspension than the laboratory-prepared materials.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) nanoparticles have shown great potential for sorption of arsenic in contaminated soil and water because of the small particle size, large specific surface area, and high sorption capacity and affinity (Yean et al, 2005;Yavuz et al, 2006;Shipley et al, 2009;An et al, 2011). To prevent nanoparticles from aggregating, and thus, to enhance sorption capacity and soil deliverability, various particle stabilization strategies have been reported (Ponder et al, 2001;Raveendran et al, 2003;Zhao, 2005, 2007;Pan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that magnetite particle size (Yean et al, 2005) and starch coating (He and Zhao, 2005) could strongly influence the arsenic adsorption capacity. However, a molecular level understanding has been lacking pertaining to the mechanisms of particle stabilization, effect of starch on the structure of SMNP, and the mode of arsenic complexation on the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the magnetic nanoparticles possess the advantages of large surface area, high number of surface active sites and magnetic properties, which lead to high adsorption efficiency, removal rate of contaminants, easy and rapid separation of adsorbent from solution via magnetic field, in addition to, the regeneration of magnetic nanoparticles and the potential reuse of the removed harmful components [14]. Investigators have shown that the magnetite nanocrystals can absorb both arsenate and arsenite at a special size range of 6-20 nm and are easily removed from solution by low-field magnets [15,16]. The nanoparticles have several advantages, such as their magnetic properties, high adsorption capacity and observed desorption hysteresis [15][16][17].…”
mentioning
confidence: 99%
“…Investigators have shown that the magnetite nanocrystals can absorb both arsenate and arsenite at a special size range of 6-20 nm and are easily removed from solution by low-field magnets [15,16]. The nanoparticles have several advantages, such as their magnetic properties, high adsorption capacity and observed desorption hysteresis [15][16][17].…”
mentioning
confidence: 99%